2018
DOI: 10.7441/joc.2018.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Development Beyond the Gfc: The Case of V4 Countries

Abstract: The stock exchanges are widely considered to be pivotal institutions providing the capital for companies and helping them to gain competitive advantage through economies of scale. This paper examines and sheds additional insight into the stock market behaviour of countries of Visegrad Group, namely the Czech Republic, Slovak Republic, Poland and Hungary, beyond the global financial crisis. The study uses data about official stock market indices of the four official stock exchanges in the Visegrad region, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
3
12
0
1
Order By: Relevance
“…Over the last few decades, global finance markets have gone through a number of financial crises, the most devastating of which include Mexican peso crisis in 1994, Asian flu in 1997, Russian crisis in 1998, Brazilian crisis in 1999, Argentinian crisis in 2001-2002, the USA financial crisis in 2007 and Greek crisis in 2009. The periods of financial contagion have evidently raised the risk of securities (Vychytilova, 2018;Mačí & Valentová Hovorková, 2017; Čulková et al, 2015;Vukovic et al, 2017) and returned the interest in gold as in alternative financial instrument since gold has historically been treated as a standard of high value. Of course, other alternative investments should be mentioned here too (Jurevičienė, & Jakanovytė, 2015;Nuhiu et al, 2017;Mouselli et al, 2016;Śliwiński & Łobza, 2017;Nawrocki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, global finance markets have gone through a number of financial crises, the most devastating of which include Mexican peso crisis in 1994, Asian flu in 1997, Russian crisis in 1998, Brazilian crisis in 1999, Argentinian crisis in 2001-2002, the USA financial crisis in 2007 and Greek crisis in 2009. The periods of financial contagion have evidently raised the risk of securities (Vychytilova, 2018;Mačí & Valentová Hovorková, 2017; Čulková et al, 2015;Vukovic et al, 2017) and returned the interest in gold as in alternative financial instrument since gold has historically been treated as a standard of high value. Of course, other alternative investments should be mentioned here too (Jurevičienė, & Jakanovytė, 2015;Nuhiu et al, 2017;Mouselli et al, 2016;Śliwiński & Łobza, 2017;Nawrocki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the conclusions from the previous studies. For example, Vychytilova (2018) showed, that the Slovak stock market was uncorrelated with other markets in the V4 group almost in all years in the post-GFC period and this was explained by the low liquidity, depth, and market capitalization of the Bratislava Stock Exchange. Baumöhl (2013) makes similar arguments and points out that the Slovak stock market may be inefficient, which is related to market capitalization and the shareholder structure.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Results from a study by Barras et al (2006), in which the relatively new false discovery rate was used to assess the performance of unit trusts, may seem disquieting to ordinary investors who are convinced of the advantages of active portfolio management. Other authors scrutinized the performance of over 2,000 mutual funds and came to the conclusion that only 0.6% of these funds proved to actually defeat the market (Barras et al, 2006;Galloppo & Aliano, 2018;Vychytilova, 2018;Sosnowski, 2018). Along with these studies, others have shown similar outcomes in recent years.…”
Section: Introductionmentioning
confidence: 94%